New Interpretation of the Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses one of the modern literary trends today, modernism and its occurrence in Uzbek literature. It is well known that modernism in literature aims to create an artistic model of the artist’s imagination instead of an image of objective reality. That is, the article mainly analyzes the fact that modernism is not a reflection of reality, but the priority of the artist's self-expression. In Uzbek literature, modernism was introduced through the theoretical views of modern artists such as Fitrat and Cholpon, and artists such as Oybek and Askad Mukhtor and the artistic skills of these artists are considered to be four aspects of independence. Thanks to independence, Uzbek literature has become free of ideology, freedom of creativity has expanded, the scope of formal and expressive experiments in literature has expanded, great horizons have been opened for the creative pursuits of the people of poetry.